Gastrin-releasing peptide in human nasal mucosa. - Baraniuk, J N (1990)
Gastrin-releasing peptide (GRP), the 27 amino acid mammalian form of bombesin, was studied in human inferior turbinate nasal mucosa. The GRP content of the mucosa measured by radioimmunoassay was 0.60 +/- 0.25 pmol/g tissue (n = 9 patients; mean +/- SEM). GRP-immunoreactive nerves detected by the immunogold method of indirect immunohistochemistry were found predominantly in small muscular arteries, arterioles, venous sinusoids, and between submucosal gland acini. 125I-GRP binding sites determined by autoradiography were exclusively and specifically localized to nasal epithelium and submucosal glands. There was no binding to vessels. The effects of GRP on submucosal gland product release were studied in short-term explant culture. GRP (10 microM) significantly stimulated the release of the serous cell-specific product lactoferrin, and [3H]glucosamine-labeled glycoconjugates which are products of epithelial goblet cells and submucosal gland cells. These observations indicate that GRP released from nerve fibers probably acts on glandular GRP receptors to induce glycoconjugate release from submucosal glands and epithelium and lactoferrin release from serous cells, but that GRP would probably not affect vascular permeability.